ASPEK SOSIAL BUDAYA MASYARAKAT BERKAITAN DENGAN KEJADIAN MALARIA DI DESA SIDOAN KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Ningsi, Ningsi; Anastasia, Hayani; Nurjana, Made Agus (Badan Penelitian dan Pengembangan Kesehatan, 2010)
Village Sidoan district Tinombo, Parigi Moutong is a malaria endemic area. Based on the residís of MBS (Mass Blood Survey) there were patients with Falciparum 85 people, patients vivax 235. Generally, residential community located near the area of rice fields, beaches, swamps, rivers and livelihoods, and mostly are farmers and fishermen. Aimed This study sofare to identify socio-cultural aspects of society includes the knowledge, attitude and behavior of the community related with malaria. The research method is qualitative method with narrative analysis. The results showed that communities knowledge about malaria particular of the causes, prevention, modes of transmission, treatment are still based on traditional knowledge. Some people still have beliefs about the causes and cures whit based on traditions. The indeep interviewed result showed that some of the informants said that caused of illness heat like malaria, fever etc caused by the four elements that is fire, earth, water and air. Communities behavior/ during the night are watching television, defecate, bathing in the river, working the fields, chatting with neighbors while playing chess and cards. Keywords: Malaria, knowledge, attitude, behaviour, Sidoan